Performance of geosynthetic reinforcement on the ballasted railway track - L. S. Sowmiya; J. T. Shahu; K. K. Gupta (International Association of Lowland Technology, 2015)
Geosynthetics provide an important option to improve track support stabilization and thereby reduce the track maintenance costs and operation costs due to train delays. In railroad construction, geosynthetics may be installed within or beneath the ballast or subballast layers. In this present study, model tests were performed on model tracks laid at 1:3 scale to the prototype with adequate thickness of subballast layer and placed on soft subgrade soils. Model tracks were adequately instrumented to record induced stresses and displacements in the track. Model tracks were reinforced with geogrid or geotextile or both at suitable interfaces. Track condition after a heavy rainfall was simulated. In this present study, three dimensional finite element analyses of geosynthetic reinforced railway track sections have been carried out using MIDAS/GTS 2013 and compared with unreinforced sections. The result shows that the reinforcement can be used to improve the performance of railway tracks on clayey subgrade.